2021
DOI: 10.1007/s12639-021-01407-9
|View full text |Cite
|
Sign up to set email alerts
|

The roles of betulinic acid on circulating concentrations of creatine kinase and immunomodulation in mice infected with chloroquine-susceptible and resistant strains of Plasmodium berghei

Abstract: Complete malarial therapy depends largely on the immunological and in ammatory response of the host to the invading potentials of malarial parasite. In this study, we evaluated the roles of betulinic acid on immunological response, anti-in ammatory potentials and concentrations of creatine kinase in mice infected with chloroquine susceptible (NK 65) and resistant (ANKA) strains of Plasmodium berghei. Serum Interlukins 1β and 6 (IL-1 β, IL-6), tumour necrosis factor alpha (TNFα), immunoglobulins G and M (IgG an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Higher CK and LDH levels and massive neutrophil infiltration are observed in animal models of muscle damage 22 , 24 - 26 . Olanlokun et al indicate that betulinic acid, one oxidized form of betulin, decreases CK activity to attenuate malaria infection-induced cardiac and skeletal injury 27 . Our data revealed that betulin treatment not only attenuated CK and LDH levels (Figure 4 ) but also blunted neutrophil infiltration in damaged sites (Figure 5 A) after contusion-induced muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Higher CK and LDH levels and massive neutrophil infiltration are observed in animal models of muscle damage 22 , 24 - 26 . Olanlokun et al indicate that betulinic acid, one oxidized form of betulin, decreases CK activity to attenuate malaria infection-induced cardiac and skeletal injury 27 . Our data revealed that betulin treatment not only attenuated CK and LDH levels (Figure 4 ) but also blunted neutrophil infiltration in damaged sites (Figure 5 A) after contusion-induced muscle injury.…”
Section: Discussionmentioning
confidence: 99%